MANAGEMENT OF COMPETITIVE ADVANTAGES IN CONFECTIONERY INDUSTRY ENTERPRISES: A CASE STUDY OF SLOVAKIA AND UKRAINE - Nataliia Parkhomenko; Lucia Vilčeková; Peter Štarchoň (Academy Review)
The global confectionery industry is one of the most dynamically developing sectors of the economy and one of the fastest-growing segments of the consumer market. This growth is driven by shifting demand, influenced by healthy eating trends, as well as the industry’s ability to adapt to consumer preferences through innovation and the development of flexible competitive strategies. This paper is based on the hypothesis that, for effective competition, enterprises in the confectionery industry must continuously monitor the business environment and implement strategic measures in a timely manner. The aim of this research is to substantiate the choice of a competitive strategy by monitoring the competitive advantages of enterprises in the confectionery industry, using Ukraine and Slovakia as case studies. The research materials include statistical data on the development of the confectionery industry in Ukraine and Slovakia from Ukrstat and Eurostat. To compare the competitive advantages of confectionery enterprises in both countries, the authors used methods such as diagnostic analysis, statistical data analysis, and case studies were employed. Expert evaluations from the confectionery industry in Ukraine and Slovakia were used to monitor and assess competitive advantages. The monitoring procedure followed a structured sequence of actions: (1) identifying development trends in the confectionery industry, (2) determining key competitive advantages, and (3) conducting an expert assessment of these advantages. Based on this assessment, priorities were established, and a competitive strategy was defined. The competitive advantages evaluated by experts included the dynamics of confectionery production, revenue growth, digitalization of sales, average product prices, operational efficiency, brand development, product innovation, ingredient safety, and export potential. The potential competitive advantages of confectionery industry enterprises, which experts were asked to evaluate, included the dynamics of confectionery production, revenue dynamics, digitalization of sales, average prices for confectionery products, efficiency, brand development, product innovation, ingredient safety, and export potential. The results of the expert assessment indicate that the confectionery enterprises of Ukraine and Slovakia have significant potential for growth and strengthening their competitive position. Ukrainian enterprises, in particular, benefit from larger production volumes, a more innovative product assortment, and higher product quality. To further enhance their competitive advantages, Ukrainian enterprises should focus on digitalizing sales and expanding into new markets to boost exports. For Slovak enterprises, increasing production volumes, digitizing sales, refining product policy to expand assortments, and diagnosing export potential are recommended strategies for gaining competitive advantages. As a result of this study, a methodological approach was developed to assess the competitive advantages of enterprises in the highly competitive confectionery industry. This approach enables enterprises in this sector to gain additional advantages in the global market. Identifying competitive advantages becomes a fundamental characteristic for providing information support in managing a company’s competitive capabilities in a global context. This article contributes to the study of methodologies for monitoring, evaluating, and managing the competitiveness of confectionery enterprises, with potential applicability to enterprises in other industries. The research also opens avenues for further studies in competitiveness management, the confectionery industry, and marketing management.